2014
DOI: 10.1158/0008-5472.can-13-2698
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Promotes Tumor Progression, Chemotherapy Resistance, and Poor Clinical Outcomes in Non–Small Cell Lung Cancer

Abstract: Toll-like receptors (TLR) recognize pathogen molecules and danger-associated signals that stimulate inflammatory processes. TLRs have been studied mainly in antigen-presenting cells, where they exert important immune regulatory functions, but they are also expressed by epithelial tumor cells, where they have been implicated in tumor progression. In this study, we demonstrate that the injection of TLR7 agonist in NOD/SCID mice, in C57BL/6 wild-type, and TLR7-deficient mice grafted with lung adenocarcinoma tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 40 publications
(43 reference statements)
6
71
1
Order By: Relevance
“…Bacterial lipopolysaccharide (LPS), an agonist of TLR4, failed to affect tumor growth (Figure 1A), while CpG, an agonist of TLR9, actually inhibited tumor growth (Figure 1B). On the contrary, intratumoral injection of the TLR7 agonist CL264 induced a pro-tumorigenic effect (Figure 1C), in accordance to our previous observations 11 .
10.1080/2162402X.2018.1505174-F0001Figure 1.Pro- or anti-tumoral effects of different TLRs stimulation.Left panel: TLR4 (A), TLR9 (B) and TLR7 (C) expression by LLC-luc cells and TLR7 expression by LLC-luc cells deficient for TLR7 (obtained by CRISPR/Cas9 technology) (D). Control isotype is shown in blue and stained cells in orange.Right panel: Tumor progression in WT C57Bl/6 mice grafted with LLC-luc cells, after LPS (A) or CpG injection (B).
…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Bacterial lipopolysaccharide (LPS), an agonist of TLR4, failed to affect tumor growth (Figure 1A), while CpG, an agonist of TLR9, actually inhibited tumor growth (Figure 1B). On the contrary, intratumoral injection of the TLR7 agonist CL264 induced a pro-tumorigenic effect (Figure 1C), in accordance to our previous observations 11 .
10.1080/2162402X.2018.1505174-F0001Figure 1.Pro- or anti-tumoral effects of different TLRs stimulation.Left panel: TLR4 (A), TLR9 (B) and TLR7 (C) expression by LLC-luc cells and TLR7 expression by LLC-luc cells deficient for TLR7 (obtained by CRISPR/Cas9 technology) (D). Control isotype is shown in blue and stained cells in orange.Right panel: Tumor progression in WT C57Bl/6 mice grafted with LLC-luc cells, after LPS (A) or CpG injection (B).
…”
Section: Resultssupporting
confidence: 92%
“…Expression of TLR7 was also validated by quantitative PCR (data not shown). We have previously demonstrated that intratumoral injection of TLR7 agonist results in increased tumor progression in immunocompetent as well as in immunodeficient mice 11 . However, the precise mechanisms involved in such pro-tumorigenic effects are elusive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations